High‐Internal‐Phase Pickering Emulsions Stabilized Solely by Peanut‐Protein‐Isolate Microgel Particles with Multiple Potential Applications. Issue 30 (3rd July 2018) - Jiao, Bo; Shi, Aimin; Wang, Qiang; Binks, Bernard P.
Abstract: High‐internal‐phase Pickering emulsions have various applications in materials science. However, the biocompatibility and biodegradability of inorganic or synthetic stabilizers limit their applications. Herein, we describe high‐internal‐phase Pickering emulsions with 87 % edible oil or 88 % n ‐hexane in water stabilized by peanut‐protein‐isolate microgel particles. These dispersed phase fractions are the highest in all known food‐grade Pickering emulsions. The protein‐based microgel particles are in different aggregate states depending on the pH value. The emulsions can be utilized for multiple potential applications simply by changing the internal‐phase composition. A substitute for partially hydrogenated vegetable oils is obtained when the internal phase is an edible oil. If the internal phase is n ‐hexane, the emulsion can be used as a template to produce porous materials, which are advantageous for tissue engineering. Abstract : Fit for consumption : Peanut‐protein‐isolate microgel particles existing at the interface and in the continuous phase inhibited the destabilization of high‐internal‐phase (87 % edible oil or 88 % n ‐hexane) oil/water Pickering emulsions (see picture). Such emulsions based entirely on natural and nontoxic raw materials could potentially be adapted for multiple applications in food and tissue engineering simply by changing the internal‐phase composition.